2020
DOI: 10.1037/tra0000704
|View full text |Cite
|
Sign up to set email alerts
|

The need for psychosocial support amid COVID-19 crises in Nigeria.

Abstract: With the closure of all public places, the stay-at-home order and the worsening economic indices occasioned by the fall in the price of crude oil with no foreseeable end, learned helplessness, negative emotions, and other psychosocial problems are bound to thrive. Interventions to improve social capital, coping resources, resilience, and good community and family cohesion are needed to promote psychosocial well-being during and after the COVID-19 pandemic in Nigeria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 9 publications
1
12
2
1
Order By: Relevance
“…Contrary to the finding in this study, other studies have reported stress and anxiety as psychological reactions due to the Coronavirus pandemic (Atalan, 2020). Other psychological reactions such as boredom, anger, and loneliness have been notably identified as resultant threats during the COVID-19 pandemic (Aluh & Onu, 2020). This calls for the provision of psychosocial support for individuals during the COVID-19 lockdown.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Contrary to the finding in this study, other studies have reported stress and anxiety as psychological reactions due to the Coronavirus pandemic (Atalan, 2020). Other psychological reactions such as boredom, anger, and loneliness have been notably identified as resultant threats during the COVID-19 pandemic (Aluh & Onu, 2020). This calls for the provision of psychosocial support for individuals during the COVID-19 lockdown.…”
Section: Discussioncontrasting
confidence: 99%
“…Such perceptions could have been influenced by several factors. Social media platforms such as WhatsApp, Facebook and Twitter have been used to spread false news on COVID-19, resulting to panic disorder and anxiety among some persons and shunning of safety measures among others (Aluh & Onu, 2020;Olapegba et al, 2020). Among many persons, physical distancing, social isolations, restriction of religious and social gatherings etc.…”
Section: Introductionmentioning
confidence: 99%
“…Nigeria being a densely populated country, is experiencing challenges related to mental health issues in the context of COVID-19. The limited existing research on mental health-related to COVID-19 discusses the impact of COVID-19 on mental health and the need for psychosocial support ( Aluh & Onu, 2020 ; Chukwuorji & Iorfa, 2020 ; Kola, 2020 ; Otu, Charles, & Yaya, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…These factors may affect social capital as well as mental health among the affected individuals. Nonetheless, the worsening economic indices with no foreseeable end, individual and collective helplessness, negative emotions, and other psychosocial challenges are thriving around the world (Aluh and Onu, 2020).…”
Section: Social Capital and Covid-19: Implications For Mental Healthmentioning
confidence: 99%